Currículos inventivos entre macro/micropolíticas: por uma vida bonita no coletivo do cotidiano escolar - Gabriel, Andrea dos Santos (2023)
The boldness of the philosophers of difference is intertwined with this research as an invitation to affirm the life that (re)exists and creates collective curricular movements in the fissures of the established curriculum. Immersed in the smells, tastes, noises and silence of everyday school life, the research maps active micropolitical movements in an elementary school in the municipality of Serra-ES, in order to problematize inventive curricular movements that can be produced in this relationship. An invitation to violate thought and experiment, instead of interpreting, a movement that breaks with the fixed idea of curriculum and opens up to thinking about curricula, as many as necessary for difference to proliferate. A bet on the strength of the collective of teachers and on conversation networks provokes us to think: What inventive curricular movements can collective bodies constitute, between macro/micropolitics, with the intention of affirming a beautiful life in everyday school life? It proposes thinking about education as a rhizome, which acts between things and slides continuously, unlike arborescent thinking that limits, frames and disregards singularities. It argues for a collective creation of curricula intertwined with the signs of art, from the perspective of creation, which opens space for the proliferation of difference, not representation. In dialogue with Deleuze and Guattari's philosophy of difference, with Carvalho's conception of curriculum and conversation networks, with Rolnik's thoughts on active micropolitics and in combination with other research with everyday life, this research focuses on curricula that act like the child in Manoel de Barros' poems and trace detours and winding paths, even in the face of the insistence to follow straight lines; CVs that, like birds, break away from their forms, fly and land when they feel the need; and curricula that, like wanderers, invent other paths, do not establish roads; curricula that are committed to the life that pulsates in everyday school life; CVs that affirm a beautiful life! In a cartography that is always open to experimentation, it is concluded that, among the forms that insist on blocking forces, teachers, collectively, create processes of resistance and problematize curricula, inventing other modes of curriculum, other ways of teaching, affirming the life that leaks, (re)exists and is beautiful!